Laboratory tests on heat treatment of ballast water using engine waste heat - Balaji, R.; Lee Siang, H.; Yaakob, O.; Koh, K.; Adnan, F.; Ismail, N.; Ahmad, B.; Ismail, Mohamed; Wan Nik, W. (Taylor & Francis Ltd., 2018)
Waste heat recovery from shipboard machineries could be a potential source for heat treatment of ballast water. Similar to a shipboard schematic arrangement, a laboratory-scale engine-heat exchanger set-up harvesting waste heat from jacket water and exhaust gases was erected to test the level of species’ mortalities. Mortalities were also assessed under experimental conditions for cultured and natural plankton communities at laboratory level. Effect of pump impellers on species’ mortalities were also tested. Exposures between 60°C and 70°C for 60 sec resulted in 80–100% mortalities. Mortalities due to pump impeller effects were observed in the range of 70–100% for zooplankton. On the laboratory-scale arrangement, >95% mortalities of phytoplankton, zooplankton and bacteria were recorded. It was demonstrated that the temperature of tropical sea waters used as secondary coolant can be raised to cause species’ mortalities, employing engine exhaust gases. The results also indicated that pump impeller effects will enhance species’ mortalities. The limitations of the shipboard application of this method would be the large ballast volumes, flow rates and time for treatment.